Water quality objectives in rivers basins: standpoints, challenges and management tools (Revista de Investigaciones Universidad del Quindío, 2010)
The continuous and relentless dumping of wastewater resulting from water uses in watersheds leads to the degradation of rivers in many hydrological basins of the world. Despite the efforts made by governmental and non-governmental offices who aim at the decontamination of wastewater in the river basins, these have not been coordinated within an integrated assessment according to the conditions in many of these basins.This article tackles standpoints, challenges, and management tools needed to achieve Water Quality Objectives (WQO) in watersheds. An analysis and reflection on the international, national and regional levels is showed. Various challenges that environmental authorities have to face are introduced in order to achieve those objectives, such as space-time variability of pollution, discontinuity and/or reliability of the information as well as socio-economic aspects. Both a Colombian and a Spanish watershed are depicted in this article. The latter is shown according to the European Water Framework Directive (WFD). Instruments for both economic and legal are presented, as well as support tools for environmental authorities in order to address the problem from an Integrated Water Resources Management (IWRM) and thus to achieve the Water Quality Objectives set in these basins.
Keywords: Objectives of Water Quality; Watersheds; Integrated Water Resources Management